Marketing audit: trends and approaches - Danko, Taras; Karavan, Al. (NTU "KhPI", 2010)
The conceptual frameworks of the marketing audit have been introduced by different contributors since the late 1950s. Nowadays when almost all companies understand the significant role of marketing in an organization they more or less efficiently implement marketing practices. The marketing audit is a fundamental part of the marketing management process. It is the major tool for marketing performance evaluation. Nevertheless, there is no single vision among researchers about how to define marketing audit and how to conduct it.

Розглянуто сучасні підходи до маркетингового аудиту. Визначено основні елементи сучасної концепції маркетингового аудиту, до яких належить аудит маркетингової стратегії, аудит маркетингової функції, аудит маркетингового середовища та оцінка результатів маркетингової діяльності. Запропоновано включити до процесу маркетингового аудиту на початковому етапі процедуру бенчмаркінгу.
Keywords: marketing practices; management process; marketing performance; significant; маркетингова стратегія; маркетингова діяльність; маркетингова ефективність; бенчмаркінг